Fuzzy tgp-closed sets and fuzzy t^* gp-closed sets - Riyadh Kareem, Noor; ., . (International Journal of Engineering and Technology, 2018)
In this paper, we aim to address the idea of fuzzy -set and fuzzy -set in fuzzy topological space to present new types of the fuzzy closed set named fuzzy -closed set and fuzzy -closed set. We will study several examples and explain the relations of them with other classes of fuzzy closed sets. Moreover, in a fuzzy locally indiscrete space we can see that these two sets are the same.Â Â